Screening of neurotransmitter receptor modulators reveals novel inhibitors of influenza virus replication - Gao, Yarou; Liu, Ge; Ma, Yirui; Su, Yue; Lian, Xiaoqin; Jiang, Lefang; Ke, Jiaxin; Zhu, Xingjian; Zhang, Mingxin; Yu, Yang; Peng, Qun; Zhao, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Influenza presents a significant public health threat, as severe cases can lead to excessive inflammation and complications such as pneumonia or acute respiratory distress syndrome. Current antiviral agents targeting viral proteins may lead to the development of resistance, highlighting the need for new agents targeting host factors. Neurotransmitter receptors are vital for cellular signaling and cell cycle modulation, making them promising antiviral therapeutic targets. Recent research has demonstrated that screening libraries of compounds aimed at these receptors can help identify inhibitors that prevent the replication of various viruses, including filoviruses and SARS-CoV-2. We screened a neurotransmitter receptor modulator library in influenza-infected U937 cells and found that many adrenergic, histamine, dopamine, and serotonin receptor agonists and antagonists exhibit antiviral activity. We identified 20 candidate compounds with IC50 values below 20 μM, suggesting a critical role for these receptors in influenza replication. Three representative compounds (isoxsuprine, ciproxifan, and rotigotine) inhibited H1N1 replication in a dose-dependent manner in multiple cell lines, and were effective against H1N1, oseltamivir-resistant H1N1, H3N2, and influenza B strains. Mechanistic studies indicated that these compounds affect virus internalization during the early infection stages. In a mouse model of lethal influenza, isoxsuprine significantly decreased lung viral titers, mitigated pulmonary inflammation, and enhanced survival rates. These findings highlight neurotransmitter receptors as potential targets for developing novel anti-influenza agents, providing a foundation for further optimization of the identified compounds as potential therapeutic agents.